BUDAYA KESELAMATAN PASIEN DAN INSIDEN KESELAMATAN PASIEN DI RUMAH SAKIT: LITERATURE REVIEW - Najihah, Najihah (Journal of Islamic Nursing, 2018)
Patient safety in health care has gained much attention since the Institute of Medicine (IOM) in 2000 published a report entitled "To Err is Human: Building a Safer Health System" which points to the death rate from KTD in hospitalized patients across America totaling 44,000- 98,000 people per year. By using a lower estimate, more people die from medical errors in a year than road accidents, breast cancer, or AIDS. Therefore, if the hospital wants to reduce the incidence of patient safety incidents then the hospital should implement a patient safety culture. The purpose of this paper is to know the application of patient safety culture related to Evidence Based patient evidence incidents. In the literature search process, used several databases such as Pubmed, PMC, NCBI, PXJ, NJEM and BMJ. Keywords included are keywords relevant to the material, namely "Patient Safety Culture", "Patient Safety Incident" and "Reporting Patient Safety Incident". From various literature findings, 12 research articles were combined and considered relevant to the topic. From various research articles it is concluded that the patient safety culture is closely related to the incidence of patient safety incidents. As the patient’s safety culture increases, the incidence of patient safety incidents can be minimized. One effort that can be made to improve the application of a patient safety culture to minimize patient safety incidents is to report patient incident safety, either KNC, KPC, KTC let alone KTD